Developing and Testing a Chart Abstraction Tool for ICU Quality Measurement. (July 2019) - Lee, Jarone; Austin, J. Matthew; Kim, Jungyeon; Miralles, Paola D.; Kaafarani, Haytham M. A.; Pronovost, Peter J.; Ghimire, Vipra; Berenholtz, Sean M.; Donelan, Karen; Martinez, Elizabeth
Quality measures are increasingly used to measure the performance of providers, hospitals, and health care systems. Intensive care units (ICUs) are an important clinical area in hospitals, given that they generate high costs and present high risks to patients. Yet, currently, few valid and clinically significant ICU-specific outcome measures are reported nationally. This study reports on the creation and evaluation of new abstraction tools that evaluate ICU patients for the following clinically important outcomes: central line–associated bloodstream infection, methicillin-resistant Staphylococcus aureus, gastrointestinal bleed, and pressure ulcer. To allow ICUs and institutions to compare their outcomes, the tools include risk-adjustment variables that can be abstracted from the chart.